Estimation of Power Exchange through 110 kV OverheadPower Lines at the Interface of the Romanian and Moldovan Power Systems - Postolaty V.; Berzan V.; Bykova E.; Bosneaga V.; Ermurachi Iu.; Grigoras Gh.; Gavrilas M.; Istrate M. (Problems of the Regional Energetics, 2018)
The purpose of this paper is to estimate the possibility of technical use of the 110 kV voltage lines (OPL) for the interconnection of the power systems of the Republic of Moldova and Romania, taking into account in the unified power system regime, which includes the power system of the CIS countries, of Moldova, Romania, Ukraine and other countries in the region.In the calculation scheme of the permanent synchronous regime of the integrated system, the interconnection zone of the Moldovan and Romanian systems was highlighted for the lines of 110 kV: Stanca-Costeşti, Ţuţora (Fai) -Ungheni and Hushi-Cioara.Transformer phase difference angle adjustment devices have been introduced in the 110 kV OPLto provide the bidirectional power shift regime. In the existing topology of electricity networks, power flows at the power system interface are directed from the Republic of Moldova to Romania.Changing the direction of the power flows is possible through the 110 kV OPLA when equipped with phase shift devices. The results of the calculations of the permanent regime have demonstrated the possibility of achieving the reciprocal power exchange regime between the interconnected power systems by adjusting the phase difference angle. It was shown the possibility of stable operation when using 110 kV overheadpowerlines as interconnection lines of the Moldovan and Romanian power systems.The issue of interconnection through the 110 kV lines is complex and requires an individual approach to how to achieve it.